Ocean warming increases availability of crustacean prey via riskier behavior. (21st November 2019) - Marangon, Emma; Goldenberg, Silvan U; Nagelkerken, Ivan
Abstract: Marine prey and predators will respond to future climate through physiological and behavioral adjustments. However, our understanding of how such direct effects may shift the outcome of predator–prey interactions is still limited. Here, we investigate the effects of ocean warming and acidification on foraging behavior and biomass of a common prey (shrimps, Palaemon spp.) tested in large mesocosms harboring natural resources and habitats. Acidification did not alter foraging behavior in prey. Under warming, however, prey showed riskier behavior by foraging more actively and for longer time periods, even in the presence of a live predator. No effects of longer-term exposure to climate stressors were detected on prey biomass. Our findings suggest that ocean warming may increase the availability of some prey to predators via a behavioral pathway (i.e., increased risk-taking by prey), likely by elevating metabolic demand of prey species. Abstract : Prey availability might increase for some predators in future oceans. Using a long-term mesocosm experiment investigating the effects of warming and acidification on prey, we show that common shrimp prey species feed more under high temperatures, even in the presence of a predator, but do not change in their biomass. The higher risk-taking behavior in prey might enhance feeding opportunities for some predators in future climate, altering predator–prey interactions and food web structure.